Glucocorticoid-Induced Leucine Zipper: Fine-Tuning of Dendritic Cells Function - Vétillard, Mathias; Schlecht-Louf, Géraldine (Frontiers in Immunology, 2018)
Dendritic cells (DCs) are key antigen presenting cells that control the induction of both tolerance and immunity. Understanding the molecular mechanisms regulating DCs commitment toward a regulatory- or effector-inducing profile is critical for better designing prophylactic and therapeutic approaches. Initially identified in dexamethasone-treated thymocytes, the Glucocorticoid-Induced Leucine Zipper (GILZ) protein has emerged as a critical factor mediating most –but not all- glucocorticoids effects in both non-immune and immune cells. This intracellular protein exerts pleiotropic effects through interactions with transcription factors and signaling proteins, thus modulating signal transduction and gene expression. GILZ has been reported to control the proliferation, survival and differentiation of lymphocytes, while its expression confers anti-inflammatory phenotype to monocytes and macrophages. In the past twelve years, a growing set of data has also established that GILZ expression in DCs is a molecular switch controlling their T-cell-priming capacity. Here, after a brief presentation of GILZ isoforms and functions, we summarize current knowledge regarding GILZ expression and regulation in DCs, in both health and disease. We further present the functional consequences of GILZ expression on DC capacity to prime effector or regulatory T-cell responses and highlight recent findings pointing to a broader role of GILZ in the fine tuning of antigen capture, processing and presentation by DCs. Finally, we discuss future prospects regarding the possible roles for GILZ in the control of DCs function in the steady state and in the context of infections and chronic pathologies.